A novel dynamic brain network in arousal for brain states and emotion analysis - Yunyuan Gao (AIMS Press, 2021)
Background: Brain network can be well used in emotion analysis to analyze the brain state of subjects. A novel dynamic brain network in arousal is proposed to analyze brain states and emotion with Electroencephalography (EEG) signals.